An unexpected protein interaction promotes drug resistance in leukemia. Issue 1 (December 2017) - Pitre, Aaron; Ge, Yubin; Lin, Wenwei; Wang, Yao; Fukuda, Yu; Temirov, Jamshid; Phillips, Aaron; Peters, Jennifer; Fan, Yiping; Ma, Jing; Nourse, Amanda; Sinha, Chandrima; et al.
Abstract The overall survival of patients with acute myeloid leukemia (AML) is poor and identification of new disease-related therapeutic targets remains a major goal for this disease. Here we show that expression of MPP1, a PDZ-domain-containing protein, highly correlated with ABCC4 in AML, is associated with worse overall survival in AML. Murine hematopoietic progenitor cells overexpressing MPP1 acquired the ability to serially replate in methylcellulose culture, a property crucially dependent upon ABCC4. The highly conserved PDZ-binding motif of ABCC4 is required for ABCC4 and MPP1 to form a protein complex, which increased ABCC4 membrane localization and retention, to enhance drug resistance. Specific disruption of this protein complex, either genetically or chemically, removed ABCC4 from the plasma membrane, increased drug sensitivity, and abrogated MPP1-dependent hematopoietic progenitor cell replating in methylcellulose. High-throughput screening identified Antimycin A as a small molecule that disrupted the ABCC4–MPP1 protein complex and reversed drug resistance in AML cell lines and in primary patient AML cells. In all, targeting the ABCC4–MPP1 protein complex can lead to new therapies to improve treatment outcome of AML, a disease where the long-term prognosis is poor. ABCC4 is a chemotherapeutic drug exporter highly expressed in acute myeloid leukemia. Here, the authors demonstrate that MPP1 anchors ABCC4 to the outer cell membrane mediating drug resistance in leukemic cells and identify antimycin A as a chemical probe that disrupts such interaction and restores sensitivity.